Pengaruh Penerapan Metode Pembelajaran Dengan Media Flash Card Terhadap Peningkatan Kemampuan Membaca Pada Anak Slow Learner - Illuminata Rheny Arum Permitasari; Djivora Chrystin Br Bangun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2021)
This research is about the influence of the application of learning methods with flash card to the improvement of reading skills of slow learner children in Kranggan Salomo Elementary School Semarang, the subject is a grade II elementary school. The experimental design used was one-group pretest-posttest design. The analysis method used is the Wilcoxon test. The result showed Z = 3,083 with p = 0,002 (p <1%), the hypothesis is accepted, there is a very significant effect of learning methods with flash card is improving reading skills in slow learner children, the reading ability pretest: mean 38,45; the posttest :mean 57.34. The results of the average reading ability before and after there are differences. The average yield increases after being given a treatment method of learning using flash card.